2021
DOI: 10.30831/akukeg.740277
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Creative Drama Method on Students’ Speaking Skills

Abstract: Aim of the research was to investigate the impact of creative method on improving students' speaking skills in primary school 3 rd grade Turkish language course. The study was carried out with primary school 3 rd graders studying at a private primary school in Çaycuma, Zonguldak. The research was carried out on forty-six 3 rd grade students. Quasi-experimental design with pretest-posttest control group was used in the study. Speaking education was given using creative drama method in the experimental group and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The fourth and fifth questions of the current study aimed at figuring out the effects of using contemporary talk shows on developing faculty of education, English majors' EFL creative speaking skills and speaking self-efficacy. EFL creative speaking skills and speaking self-efficacy have been found necessary for EFL language learners as confirmed by a number of studies as (Alan & Peachy, 2018;Au & Badakci, 2020;Becker & Roos, 2016;Culha, 2020;Demirel & Aydin, 2020;Frey & Vallade, 2018;Hayran, 2020;Ozenc, Orhan-Karsak & Ozenc, 2021;Ozturk-Pat & Yilmaz, 2021). The purpose of the current study was to determine the effects of using contemporary talk shows on developing EFL creative speaking skills and speaking self-efficacy for faculty of education, English majors.…”
Section: Discussionmentioning
confidence: 80%
“…The fourth and fifth questions of the current study aimed at figuring out the effects of using contemporary talk shows on developing faculty of education, English majors' EFL creative speaking skills and speaking self-efficacy. EFL creative speaking skills and speaking self-efficacy have been found necessary for EFL language learners as confirmed by a number of studies as (Alan & Peachy, 2018;Au & Badakci, 2020;Becker & Roos, 2016;Culha, 2020;Demirel & Aydin, 2020;Frey & Vallade, 2018;Hayran, 2020;Ozenc, Orhan-Karsak & Ozenc, 2021;Ozturk-Pat & Yilmaz, 2021). The purpose of the current study was to determine the effects of using contemporary talk shows on developing EFL creative speaking skills and speaking self-efficacy for faculty of education, English majors.…”
Section: Discussionmentioning
confidence: 80%
“…It is important to be used body language, gestures, and mimics in the creative drama method. Since these skills are also taken into consideration in the practices, the awareness of the students on this issue develops (Öztürk-Pat & Yılmaz, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, it was concluded that creative drama positively affects academic achievement and attitude towards the lesson. Within the context of language teaching, it has been concluded that creative drama is an effective method in developing students' language skills (Aykaç & İlhan, 2014;Galente & Thomson, 2017;Jie, 2021;Susar-Kırmızı, 2015;Öztürk-Pat & Yılmaz, 2021;Terzioğlu-Ünveren, 2018;Türkel & Öz, 2020), vocabulary (Arpağ, 2018;Kır-Cullen, 2021;Koçpınar, 2018;Metinnam & Erdoğan, 2016, Şahin, 2018Şenol, 2011) and in the teaching of grammar (Kodaz, 2007;Özkaya and Altuntaş, 2021;Şimşek et al, 2010;Teke & Gedizli, 2016;Türkel & İnnalı, 2020;Yeşilyurt, 2011) and that it increases students' interest in the lesson (Aytaş & Özcan, 2019;Keşaplı, 2019;Kurudayıoğlu & Özdem, 2015;Özcan, 2020). There are also experimental studies examining the effects of creative drama on students' attitudes towards Turkish lessons and Turkish language skills (Çam-Türkan, 2020;Erden, 2016;Erdoğan, 2013;Erdoğan, Erdoğan & Uzuner, 2018;Ergüder, 2019;Erkan & Aykaç, 2014;İsbir-Abrekoğlu, 2019;Kara, 2010;Kardaş, 2018;Kılıç, 2018;Öz, 2018;Özber, 2019;Susar-Kırmızı, 2008;Tanrıkulu & Yoğurtçu, 2018...…”
Section: Yaratıcı Dramanın Türkçe Dersine Ve Türkçe Dil Becerilerine ...mentioning
confidence: 99%